Soil Enzyme Activity in Soils Subjected to Flooding and the Effect on Nitrogen and Phosphorus Uptake by Oilseed Rape - Gu, Chiming; Zhang, Shujie; Han, Peipei; Hu, Xiaojia; Xie, Lihua; Li, Yinshui; Brooks, Margot; Liao, Xing; Qin, Lu (Frontiers in Plant Science, 2019)
Waterlogging presents one of the greatest constraints for agricultural crops. In order to elucidate the influences of waterlogging stress on the growth of oilseed rape, a pot experiment was performed investigating the impact of waterlogging on nitrogen (N) and phosphorus (P) accumulation in oilseed rape, and mineral N and available P profiles and enzyme activities of soils. The experiment included waterlogging treatments lasting 3 (I), 6 (II) and 9 (III) days, and a control treatment without waterlogging (CK). Results showed that waterlogging lasting 3 or more days significantly depressed the growth of oilseed rape, and prolonged the recovery time of plant growth with the period of flooding. Waterlogging notably influenced the N and P concentrations in plant tissues, and also affected mineral N, available P profiles and activities of enzymes (including urease, phosphatase, invertase and catalase) in the soils. With the exception of catalase, flooding suppressed the activity of urease, phosphatase, and invertase to varying degrees, and the longer the flooding time, the greater the suppression. The effect of waterlogging on mineral N and P profiles resulted from the altered proportions of NH4+-N and NO3--N, and the decreased available P concentrations in these soils, respectively. The effect on P was more significant than on N in both soil nutrient profile and plant utilization.